The Correlation between Self Assessment and Motivation in Learning English of the Second Grade Students of SMP Negeri 6 Palembang - Munjiana, Munjiana (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2018)
AbstractThere is no single magical formula for motivating students. Many factors affect a given student'smotivation to work and to learn. This study focused on the correlation between self assessmentand motivation in learning English of the Second Grade students of SMPN 6 Palembang. Thereare four objectives in this study:1) to find out how the second grade students of SMP N6Palembang motivation in learning English is; 2) to find out how the second grade students ofSMPN 6 Palembang self assessment is; 3) to find out whether or not there is any significantcorrelation between self assesment and motivation in learning English of The Second GradeStudents of SMPN6 Palembang; and 4) How much self assesment contribute to Students’motivation in learning English of The Second Grade Students of SMPN 6 Palembang. The datawere collected by using questionnaire of 70 students that were taken as the samples by usingrandom sampling. Then, it was analyzed by using Person’s Product Moment CorrelationCoefficient and the calculation was done by using SPSS (Statistical Package for Social Science).The result of the study showed that 72.9% of the second grade students of SMP N6 Palembanghad good motivation in learning English and 67.1% of the second grade students of SMPN 6Palembang also had good self assessment. In addition, the degree of correlation coefficientproved strong with the value of correlation 0.715 and self assessment itself contributed 51.1% tothe students’ motivation in learning English. From the above explanation, self assessmentproved significantly has a very important role in learning language especially English.Keywords: motivation, self assessment, English learning